Functional Profiling of Chondrogenically Induced Multipotent Stromal Cell Aggregates Reveals Transcriptomic and Emergent Morphological Phenotypes Predictive of Differentiation Capacity. (7th August 2018) - Lam, Johnny; Bellayr, Ian H.; Marklein, Ross A.; Bauer, Steven R.; Puri, Raj K.; Sung, Kyung E.
Abstract : Multipotent stromal cells (MSCs) are an attractive cell source for bone and cartilage tissue repair strategies. However, the functional heterogeneity of MSCs derived from different donors and manufacturing conditions has limited clinical translation, emphasizing the need for improved methods to assess MSC chondrogenic capacity. We used functionally relevant morphological profiling to dynamically monitor emergent morphological phenotypes of chondrogenically induced MSC aggregates to identify morphological features indicative of MSC chondrogenesis. Toward this goal, we characterized the morphology of chondrogenically stimulated MSC aggregates from eight different human cell-lines at multiple passages and demonstrated that MSC aggregates exhibited unique morphological dynamics that were both cell line- and passage-dependent. This variation in 3D morphology was shown to be informative of long-term MSC chondrogenesis based on multiple quantitative functional assays. We found that the specific morphological features of spheroid area, radius, minimum feret diameter, and minor axis length to be strongly correlated with MSC chondrogenic synthetic activity but not gene expression as early as day 4 in 3D culture. Our high-throughput, nondestructive approach could potentially serve as a tool to identify MSC lines with desired chondrogenic capacity toward improving manufacturing strategies for MSC-based cellular products for cartilage tissue repair.